Metabolomic Profiling of Cultured-Yeast and Spontaneously Fermented Coffees - Catherine Kiefer; Steffen Schwarz; Sascha Rohn; Philipp Weller (Proceedings)
Coffea arabica and C. canephora with all varieties make up for the largest share of cultivated coffee worldwide, whereas the C. liberica species only represents a minor proportion. This is mainly because the taste profiles of C. canephora and C. liberica varieties are typically less popular than those of C. arabica coffees. However, with evolving coffee fermentation methods, the sensory profiles of the three coffee species have advanced into more complex profiles with fewer off-flavors and, as such, have altered this traditional distribution. Pure culture yeasts partially suppress the growth of unwanted microorganisms and alter the composition of organic precursor compounds, which ultimately leads to better, more favorable sensory profiles of roasted coffee. This substantially boosts the quality of so far less popular Coffea species. Our study described a cross-platform metabolomic approach for the evaluation of the changes in the sensory metabolomes of green and roast coffees. The approach was designed in a comprehensive manner for the volatile fraction (“volatilome”) and the soluble fraction (classical metabolome). For the analysis of the volatilome, GC-MS, as well as GC-IMS, was utilized. The non-volatile compounds were analyzed and tentatively identified with LC-HRMS, paired with metabolomic tools. The first results from the volatilomics platform showed substantial differences in the volatile organic compound (VOC) profile of controlled fermented and wild fermented coffees. Preliminary orthogonal analyses based on non-targeted HPLC-ESI-HRMS tentatively allowed for the identification of individual substance groups that showed process-specific formation or breakdown during controlled coffee fermentation. The data from all platforms were evaluated and compared. Through this approach, a holistic and complementary view of the volatile and non-volatile metabolomes of cultured-yeast and spontaneously fermented coffees was accomplished. This study presents direct comparisons of the metabolomic analysis of different types of fermentation approaches for coffees, and the first results of the metabolomic platform will be shown. An outlook on the future and the relevance of fermentation for the flavor enhancement of coffee will be given.